2011
DOI: 10.1371/journal.pone.0026879
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Cell Division and Notch Signaling Specify Dopaminergic Neurons in Drosophila

Abstract: In Drosophila, dopaminergic (DA) neurons can be found from mid embryonic stages of development till adulthood. Despite their functional involvement in learning and memory, not much is known about the developmental as well as molecular mechanisms involved in the events of DA neuronal specification, differentiation and maturation. In this report we demonstrate that most larval DA neurons are generated during embryonic development. Furthermore, we show that loss of function (l-o-f) mutations of genes of the apica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Interestingly, most of these neurons are collinear with the H-cell suggesting that the same segmentation genes that control H-cell development also play a role in paramedial and dorsal lateral neuron development. Consistent with this view, recent work (Tio et al, 2011) has indicated that both DA neurons are wg + , which overlaps in lateral CNS expression with gsb and slp1/2 , L(1)sc is ectopically present in MP1 neurons (blue arrow; only one MP1 neuron is shown), as well as in the H-cell and H-cell sib (yellow arrows) and AMG (white asterisks).…”
Section: Genes Controlling Mp3 Development Are Also Required For the supporting
confidence: 58%
“…Interestingly, most of these neurons are collinear with the H-cell suggesting that the same segmentation genes that control H-cell development also play a role in paramedial and dorsal lateral neuron development. Consistent with this view, recent work (Tio et al, 2011) has indicated that both DA neurons are wg + , which overlaps in lateral CNS expression with gsb and slp1/2 , L(1)sc is ectopically present in MP1 neurons (blue arrow; only one MP1 neuron is shown), as well as in the H-cell and H-cell sib (yellow arrows) and AMG (white asterisks).…”
Section: Genes Controlling Mp3 Development Are Also Required For the supporting
confidence: 58%
“…Spana and Doe, 1996; Tio et al, 2011). In the NB7-3 lineage, daughter cells of the GMC-1 also take distinct fates, one interneuron (EW1) and the other motor neuron (GW), depending on the inheritance of Numb.…”
Section: Discussionmentioning
confidence: 99%
“…The first study to show the link between both asymmetric division machinery and Notch signaling and specification of a neurotransmitter neuronal phenotype was performed in Drosophila by Tio et al [21]. Findings from this study showed that loss of function of the proteins Inscuteable and Bazooka resulted in an excess number of dopaminergic neurons.…”
Section: The Role Of Notch Signaling During Neurogenesismentioning
confidence: 99%
“…Findings from this study showed that loss of function of the proteins Inscuteable and Bazooka resulted in an excess number of dopaminergic neurons. On the other hand, loss of function of basally distributed proteins such as Numb resulted in a reduction of dopaminergic neurons [21]. Additionally, loss of Notch signaling results in an excess amount of this neuronal phenotype, and vice versa.…”
Section: The Role Of Notch Signaling During Neurogenesismentioning
confidence: 99%